The university administration by way of financial -economic activity of controlling environment structure PRiNCE-2 - Жованик B. I. (Eastern-European Journal of Enterprise Technologies, 2012)
Is based on model achievement – a scheme of regulation and financial criteria – economic efficiency and envisages building block – design algorithm for resource management as controlling the structure methodologies PRiNCE-2